Dynamic Linkages Between Kazakhstan and Its Major Trading PArtners' Stock Market - Zhulanov, Bekezhan (2011)
This paper examines the linkages among stock markets of six countries. Kazakhstan stock market was chosen as dependant variable. Other five stock markets represent trade partner countries’ markets, namely Russia, Ukraine, US, China, Turkey. Particular study implemented Johansen – Juselius (1990) technique to investigate the cointegration between variables and Granger causality test (1969) to determine the causal relationship among stock markets. Trace test within cointegration approach identified the two cointegrating equations among variables, which implies the existence of long run equilibrium relationship among six stock markets. Granger causality test determined the bilateral causal relationships between stock markets of Kazakhstan and Russia, Kazakhstan and Ukraine, Kazakhstan and US. There is unidirectional relationship between Chinese and Kazakhstan stock markets. Granger test did not find any causal relationship between stock markets of Kazakhstan and Turkey.